Utilization of de-oiled algal biomass for enhancing vehicular quality biodiesel production from Chlorella sp. in mixotrophic cultivation systems. (July 2018) - Katiyar, Richa; Bharti, Randhir K.; Gurjar, B.R.; Kumar, Amit; Biswas, Shalini; Pruthi, Vikas
Abstract: The investigation first time reports the efficacy of de-oiled algal biomass extract (DOABE) for mixotrophic cultivation of Chlorella sp. MCC27 to enhance biodiesel production in open tray systems and in BioXpert-V2 software connected photobioreactor (PBR). The cultivation systems with addition of DOABE (PBR systems + DOABE and open tray system + DOABE) as media were tested for quality and quantity of biodiesel. The presence of organic carbon and low nitrogen in DOABE caused >2 folds higher biomass productivity and >4 folds enhanced lipid productivity for the cells cultivated in PBR system + DOABE and open tray system + DOABE as compared to control (i.e. BBM). Biochemical analysis of cells from both the systems revealed the decrease in total carbohydrates and protein contents. The FAMEs analyses showed vehicular quality biodiesel. PBR system + DOABE showed edge over open tray system + DOABE in terms of biomass productivity and lipid content. The physical properties of biodiesel produced from Chlorella sp. MCC27 were more close to the fuel standards (ASTM D6751), when cells were cultivated in open tray system + DOABE than in PBR system + DOABE. Collectively, this study highlights the use of DOABE as a low cost feedstock for enhancing vehicular quality biodiesel production from microalgae. Graphical abstract: Image 1 Highlights: Using de-oiled algal biomass extracts (DOABE) for mixotrophic cultivation of algae PBR system + DOABE and open tray system + DOABE used to enhance biodiesel production Enhancement in lipid accumulation, biomass and lipid productivity of algal cells Open tray system + DOABE showed edge over PBR system + DOABE for quality of biodiesel